2009
DOI: 10.1002/pen.21526
|View full text |Cite
|
Sign up to set email alerts
|

Structure of blown films of polyethylene/polybutene‐1 blends

Abstract: The structure of blown films of blends of low-density polyethylene (PE-LD) and isotactic polybutene-1 (iPB-1) with different content of iPB-1 was investigated using wide-and small-angle X-ray scattering (WAXS and SAXS), transmission electron microscopy (TEM), and polarizing optical microscopy (POM). TEM proves formation of a matrix-particle phase structure due to immiscibility of the blend components. Within the iPB-1 particles, needle-like crystals with c-axis orientation were observed. The PE-LD matrix showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…This superimposed orientation resulted in differences in the tensile responses of the films when tested in machine and cross-machine directions. Similar findings were reached by Godshall et al (2003) and Nase et al (2010). Zhang et al (2004) studied low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE) and HDPE films 25-100 ìm thick and found that the crystal morphology and orientation for these films are dependent on the take-up ratio (i.e., the stress applied during the manufacturing process).…”
Section: Introductionsupporting
confidence: 70%
“…This superimposed orientation resulted in differences in the tensile responses of the films when tested in machine and cross-machine directions. Similar findings were reached by Godshall et al (2003) and Nase et al (2010). Zhang et al (2004) studied low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE) and HDPE films 25-100 ìm thick and found that the crystal morphology and orientation for these films are dependent on the take-up ratio (i.e., the stress applied during the manufacturing process).…”
Section: Introductionsupporting
confidence: 70%
“…Polyethylene (PE) films have been extensively investigated for decades and it is formally known that mechanical and fracture mechanics properties strongly depend, among others, on the crystalline phase orientation, which, in turn, is controlled by the processing conditions. [1][2][3][4][5][6][7] The crystalline phase orientation in blown films is complicated due to variable, sequential transverse and axial loadings. This causes crystal re-orientation during processing before cooling fixes the final structure.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6(a,b) are images of needle-shaped deposits of alphacypermethrin present in optical micrographs taken on 1:1 m/m LDPE/ HDPE and LDPE films, respectively. The image in Figure 6(b) was captured with the sample placed between crossed polarisers, showing a rather dark/greyish appearing polymer matrix due to its semi-crystallinity and orientation of the macromolecules (Nase et al, 2010). Individual polymer crystals are too small to be detected in the distinct spherulitic crystalline-amorphous superstructure, typical for semi-crystalline PE crystallized from the quiescent melt, and is not seen due to crystallization during film blowing.…”
Section: 2mentioning
confidence: 99%